Deflationary financial shocks and inflationary uncertainty shocks: An SVAR investigation - Roberto A. De Santis; Wouter Van der Veken (European Central Bank (ECB), 2022)
What are the economic implications of financial and uncertainty shocks? We show that financial shocks cause a decline in output and goods prices, while uncertainty shocks cause a decline in output and an increase in goods prices. In response to uncertainty shocks, firms increase their markups, in line with the theory of self-insurance against being stuck with too low a price. This explains why goods prices may increase at the onset of a recession and are not accompanied by pronounced deflationary pressures. The two shocks are identified jointly with an approach that is less restrictive than Antolín-Díaz and Rubio-Ramírez's method.
Keywords: C32; E32; 330; Business cycles; financial shocks; uncertainty shocks; SVAR; narrative identification